Diagnosis of Herpes Simplex Virus: Laboratory and Point-of-Care Techniques - Peuli Nath; Md Alamgir Kabir; Somaiyeh Khoubafarin Doust; Aniruddha Ray (MDPI AG, 2021)
Herpes is a widespread viral infection caused by the herpes simplex virus (HSV) that has no permanent cure to date. There are two subtypes, HSV-1 and HSV-2, that are known to cause a variety of symptoms, ranging from acute to chronic. HSV is highly contagious and can be transmitted via any type of physical contact. Additionally, viral shedding can also happen from asymptomatic infections. Thus, early and accurate detection of HSV is needed to prevent the transmission of this infection. Herpes can be diagnosed in two ways, by either detecting the presence of the virus in lesions or the antibodies in the blood. Different detection techniques are available based on both laboratory and point of care (POC) devices. Laboratory techniques include different biochemical assays, microscopy, and nucleic acid amplification. In contrast, POC techniques include microfluidics-based tests that enable on-spot testing. Here, we aim to review the different diagnostic techniques, both laboratory-based and POC, their limits of detection, sensitivity, and specificity, as well as their advantages and disadvantages.